Genomic Insights into Pluralibacter gergoviae Sheds Light on Emergence of a Multidrug-Resistant Species Circulating between Clinical and Environmental Settings - João Pedro Rueda Furlan; Eliana Guedes Stehling (Pathogens, 2023)
Pluralibacter gergoviae is a member of the Enterobacteriaceae family that has been reported sporadically. Although P. gergoviae strains exhibiting multidrug-resistant profiles have been identified an in-depth genomic analysis focusing on antimicrobial resistance (AMR) has been lacking, and was therefore performed in this study. Forty-eight P. gergoviae strains, isolated from humans, animals, foods, and the environment during 1970–2023, were analyzed. A large number of single-nucleotide polymorphisms were found, indicating a highly diverse population. Whilst P. gergoviae strains were found to be circulating at the One Health interface, only human and environmental strains exhibited multidrug resistance genotypes. Sixty-one different antimicrobial resistance genes (ARGs) were identified, highlighting genes encoding mobile colistin resistance, carbapenemases, and extended-spectrum β-lactamases. Worryingly, the co-occurrence of mcr-9.1, blaKPC-2, blaCTX-M-9, and blaSHV-12, as well as mcr-10.1, blaNDM-5, and blaSHV-7, was detected. Plasmid sequences were identified as carrying clinically important ARGs, evidencing IncX3 plasmids harboring blaKPC-2, blaNDM-5, or blaSHV-12 genes. Virulence genotyping underlined P. gergoviae as being a low-virulence species. In this regard, P. gergoviae is emerging as a new multidrug-resistant species belonging to the Enterobacteriaceae family. Therefore, continuous epidemiological genomic surveillance of P. gergoviae is required.